Analisis Redaman pada Jaringan Fiber to the Home (FTTH) Berteknologi Gigabit Passive Optical Network (GPON) di PT Telkom Makassar - Andi Nurul Ulfawaty Z; Fausiah Fausiah (Ainet : Jurnal Informatika, 2019)
The development of telecommunications technology as a communication necessity at this time has been growing rapidly, needed a means of transmission media that is able to distribute information with large capacity and capable data transfer speeds. Implementing using Gigabit Passive Optical Network (GPON) technology, the Fiber to The Home (FTTH) service reaches the user to meet the speed of 2GBps. This study aims to identify the causes of increased attenuation or disturbance in FTTH. The method used in this study is to analyze the attenuation value of each core at the sites studied on the FTTH network at PT Telkom. The total attenuation value of fiber optic cables that are calculated from OLT to ONT must be within the specified reasonable limit of 15-28 dB. The caused of the increase in the attenuation value of fiber optic cables such as the number of splice / connections on each cable, and the occurrence of cable indentations above 45°. To overcome the attenuation value that exceeds the reasonable limit can be done by replacing the fiber cable with attenuation of 0.35dB to fiber cable with attenuation of 0.22 dB, so that the attenuation of the fiber optic cable is at the specified reasonable limit.